Effects of Anti-G and Anti-F Antibodies on Airway Function after Respiratory Syncytial Virus Infection - Han, Junyan (American Thoracic Society, 2014)
Respiratory syncytial virus (RSV) is the leading cause of lower respiratory tract illnesses in infants worldwide. Both RSV-G and RSV-F glycoproteins play pathogenic roles during infection with RSV. The objective of this study was to compare the effects of anti–RSV-G and anti–RSV-F monoclonal antibodies (mAbs) on airway hyperresponsiveness (AHR) and inflammation after primary or secondary RSV infection in mice. In the primary infection model, mice were infected with RSV at 6 weeks of age. Anti–RSV-G or anti–RSV-F mAbs were administered 24 hours before infection or Day +2 postinfection. In a secondary infection model, mice were infected (primary) with RSV at 1 week (neonate) and reinfected (secondary) 5 weeks later. Anti–RSV-G and anti–RSV-F mAbs were administered 24 hours before the primary infection. Both mAbs had comparable effects in preventing airway responses after primary RSV infection. When given 2 days after infection, anti–RSV-G–treated mice showed significantly decreased AHR and airway inflammation, which persisted in anti–RSV-F–treated mice. In the reinfection model, anti–RSV-G but not anti–RSV-F administered during primary RSV infection in neonates resulted in decreased AHR, eosinophilia, and IL-13 but increased levels of IFN-γ in bronchoalveolar lavage on reinfection. These results support the use of anti–RSV-G in the prevention and treatment of RSV-induced disease.